Association of cortisol serum levels as a prognostic factor in threat of pre-term birth - Joya, Francisco R.; Ortiz, Jose Daniel Gonzalez; Bandala, Cindy R.; Gutierrez, Marlene de la Peña; Sosa, Maria Isabel Tolentino; Vilchis, Arturo B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Prematurity is one of the leading causes of death in children. In Mexico there is a frequency of 12% of preterm birth and this leads to significant maternal-fetal complications comprising 31.5% of neonatal morbidity and mortality. The patient who receives obstetric care in the gynecology service at the naval medical center requires prevention, diagnosis and treatment of threat of preterm birth to reduce perinatal and neonatal complications. Serum cortisol levels was determined as a prognostic factor for the threat of preterm birth in patients with obstetric care at the Naval Medical Center, it is a relatively easy parameter to obtain and would support a timely treatment. Methods: We used a quantitative, non-experimental, retrospective descriptive study of 30 patients with risk factors to develop preterm birth threats in gynecology service of the naval medical center from January to December 2018, which were taken 3 milliliters of peripheral blood to measure serum cortisol concentrations for later analysis. For statistical analysis of the present study, it was used Shapiro Wilk test. Likewise, Pearson's test was performed to measure the degree of association between the dependent and independent variable. Student's t-test was implemented to compare cortisol levels of pregnant women. Results: A total of 30 patients of these were analyzed, the mean age was 30.4 years (SD±5.184). The gestation weeks the average value was 30.63 weeks (SD±4.781). A student t test was performed where the cortisol values of pregnant women were compared with an average value of 2,586 (95% CI 0.45-472) and a t value=2,476 and a p=0.019 lower value of the significance value of 0.05 rejecting the null hypothesis. Which indicates that cortisol levels can be used as a predictive marker of the threat of preterm birth, considering it as an independent factor for this situation to occur in pregnant patients. The variables of the cortisol level and the weeks of gestation Pearson=-0.061 and a significance of p=0.747 were correlated (there being no strong enough relationship between the study variables). Regarding the triggers, it is observed that the highest factor was for urinary tract infection 40% n=12, abnormal uterine activity 20% n=6, followed by premature membrane rupture 16.7% n=5. Conclusions: The risk factors associated with the threat of preterm birth can be multiple, encompassing them in three important areas such as socioeconomic, psycho-emotional and clinicopathological, of the latter, nine of which are most frequent in our population are urinary infection, abnormal uterine activity and premature rupture of membranes. Regarding the association of cortisol levels as a prognostic factor for the threat of preterm birth taking it into account as an independent factor, it can be concluded that it is not statistically significant, however, according to what is reported in the literature, It should be considered as one of the multiple risk factors, considering this timely premise to boost the development of new research in the field.